Mediating Role of Cognitive Emotion Regulation Strategies in the Relationship Between Anxiety and Body Image in Women With Breast Cancer Volunteered for Mastectomy - Rohollah Zali; Ali Esmaeili; Haydeh Saberi (Gonabad University of Medical Sciences, 2022)
Background: The loss of breast is a major concern for women with breast cancer volunteer for mastectomy, because they feel that their feminine identity is at risk of damage. The present study aims to investigate the mediating role of Cognitive Emotion Regulation (CER) in the relationship between anxiety and body image in women with breast cancer volunteered for mastectomy. Methods: The is a correlational study. The study population consists of all women with breast cancer volunteered for mastectomy referred to Imam Khomeini and Imam Hossein hospitals in Tehran, Iran. Of these, 350 volunteers were selected by a convenience sampling method. The instruments were Beck Anxiety Inventorry, Body Image and Relationship Scale of Hormes et al., and Cognitive Emotion Regulation Questionnaire of Garnefski et al. Structural equation modeling were used to analyze the research hypotheses. Results: Anxiety had a positive effect on maladaptive CER strategies (β=0.654) and a negative effect on body image (β=-0.574) (P<0.001). The direct effect of maladaptive CER strategies on body image was positive and significant (β=0.271, P<0.05). The direct effects of anxiety on adaptive CER strategies (β=-0.836) and body image (β=-0.849) were negative and significant (P<0.001). The direct effect of adaptive CER strategies on body image was negative and significant (β=-0.266, P<0.001). Conclusion: Women undergoing mastectomy will experience more anxiety and negative body image if they use maladaptive CER strategies, while those who use adaptive CER strategies will experience less anxiety and negative body image.